NATIVE SPEAKER IN TEACHING ENGLISH TO INDONESIAN STUDENTS AT ICP FMIPA UNM - Nurfajrih Ningsih (ETERNAL (English, Teaching, Learning and Research Journal), 2017)
The aim of this paper is to find out the method applied by the native speaker in teaching English to Indonesian students at ICP FMIPA UNM. This research was case study. The subject of the research is a native spekear who teach at ICP FMIPA UNM. The result of the research shows that The procedures of teaching applied by native speaker in teaching English to Indonesian students at ICP UNM are the procedure required by direct method, ausdion lingual mehod, and communicative language teaching. Besides, the lecturer varied activities in each meeting through some kind of activities. The lecturer also always applied two main activities in each meeting.